Cholecalciferol (vitamin D3): efficacy, safety, and implications in public health - Ortiz-Prado, Esteban; Vasconez-Gonzalez, Jorge; Izquierdo-Condoy, Juan S.; Suárez-Sangucho, Isaac A.; Prieto-Marín, José Guillermo; Villarreal-Burbano, Karen Bereniss; Barriga-Collantes, Mateo Alejandro; Altamirano-Castillo, John Alexander; Borja-Mendoza, Domenic Anahi; Pazmiño-Almeida, Jean Carlo; Cadena-Padilla, María Paz (Frontiers in Nutrition, 2025)
Vitamin D₃ (cholecalciferol) is a fat-soluble secosteroid with essential roles in calcium-phosphorus metabolism, bone health, and an expanding range of extraskeletal processes. Upon synthesis in the skin via ultraviolet B exposure or ingestion from dietary sources, cholecalciferol is hydroxylated in the liver and kidneys to form its active metabolite, calcitriol (1,25-dihydroxyvitamin D), which exerts pleiotropic effects through vitamin D receptor (VDR)-mediated genomic and non-genomic pathways. This narrative review synthesizes evidence on the systemic effects of high-dose cholecalciferol on bone health, metabolism, cardiovascular and immune function, and its emerging roles in neurological, gastrointestinal, reproductive, oncologic, and psychiatric disorders. High-dose vitamin D₃ has demonstrated benefits in specific populations, including improved bone mineral density, immune homeostasis, glycemic control, and reduced inflammation. In patients with chronic kidney disease, cystic fibrosis, and inflammatory bowel disease, targeted supplementation has been associated with clinical improvements. Preclinical models support calcitriol’s antiproliferative and neuroprotective functions, and its synergistic effects with chemotherapy, although large-scale randomized controlled trials (RCTs) have yielded mixed or inconclusive results, particularly in cancer, cardiovascular events, and cognitive decline. Methodological variability—such as inconsistent dosing regimens, baseline vitamin D status, and heterogeneous populations—limits definitive conclusions. While vitamin D supplementation is generally safe within recommended limits, excessive intake may cause hypercalcemia or nephrolithiasis, emphasizing the need for personalized strategies. Food fortification and targeted screening remain underutilized yet cost-effective public health interventions. Overall, vitamin D₃ represents a promising but complex therapeutic agent, necessitating further rigorously designed clinical trials to establish evidence-based guidelines for its use in diverse pathological conditions.